Perbedaan Self Tapping Dan Senam Dismenore Terhadap Perubahan Tingkat Dismenore Primer Pada Mahasiswi Putri - Priatiningrum, Aisah Catur; Elsanti, Devita (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: Menstruation is a physiological matter on female that occurs from menarche to menopause. Primary dysmenorrhea is menstrual cramps without any disorders in reproductive or gynecological organs, but caused by excessive uterine contractions. Non-pharmacological management such as self tapping and dysmenorrhea gymnastics may relieve dysmenorrhea. This research aims to find out the difference between self tapping and dysmenorrhea gymnastics towards the level change of primary dysmenorrhea on female adolescents. Methods: This research used quantitative method of pre-experimental design with two group pretest posttest design. Sampling technique used central limit theorem method with 30 respondents of self tapping intervention and 30 respondents of dysmenorrhea gymnastics intervention. The sample total was 60 respondents. The research instrument used was Numeric Rating Scale (NRS). Bivariate analysis used Wilcoxon test and Mann-Whitney test. Results: The research result shows the difference between self tapping and dysmenorrhea gymnastics towards the level change of primary dysmenorrhea with p of 0.007 (p<0.05) on Mann-Whitney test. Self tapping is more effective than dysmenorrhea gymnastics. Conclusion: It can be concluded that there is a difference between self tapping and dysmenorrhea gymnastics towards the level change of primary dysmenorrhea on female adolescents.